Optimalisasi Pelayanan Fiskus dan Sanksi Perpajakan sebagai Upaya Peningkatan Kepatuhan Wajib Pajak dengan Kesadaran Wajib Pajak sebagai Variabel Mediasi - Rika Adriyana; Wahyu Puji Lestari (Jurnal Ekonomi dan Bisnis, 2022)
This study aims to determine whether tax services and tax sanctions can affect taxpayer compliance with taxpayer awareness as a mediating variable. This research was conducted at the KPP Pratama Pekalongan City, with the object of research being taxpayers who have MSME businesses in the Pemalang Regency area. The sample used in this study was 100 respondents. The type of research is quantitative. The analysis technique uses the Warppls version 5.0 application. The results of this study indicate that the tax service has a positive effect on taxpayer awareness while tax sanctions have a negative and significant effect on taxpayer awareness. Fiscal services have a positive and significant effect on taxpayer compliance. Meanwhile, tax awareness and sanctions have no significant effect on taxpayer compliance. Therefore, taxpayer awareness cannot mediate the relationship between tax service and tax sanctions on taxpayer compliance.